Introduction: Prosody in the Nordic languages. Issue 2 (18th September 2015) - Horne, Merle; Roll, Mikael
Abstract : The initiative for this special issue on prosody in the Nordic languages developed in connection with an international symposium on prosody which took place in Lund on 2–3 June 2014 (http://konferens.ht.lu.se/en/bruce-2014/ ). The symposium commemorated the life and work of Gösta Bruce (1947–2010), our friend, teacher, mentor, and colleague during many years. Gösta's contributions to the field of prosody have been of utmost significance to the development of prosody research, in particular his work on modelling the structure and function of Swedish word accents 'in sentence perspective'.